Group Farming - means to end Poverty and Hunger inVillages - Sreeni, K.R. (Journal of Agricultural Extension Management, 2019)
Amrita Sadivaiyal Vyavasayam Kulu, a group comprising of twenty farmers, belonging to the tribal community of Irulas, initiated organic farming at Sadivaiyal, a tribal hamlet in the suburbs of Coimbatore, Tamil Nadu. This paper explores the case of organic agriculture in a tribal village in Tamil Nadu. Amrita SeRVe is an initiative launched by the Mata Amritanadamayi Math. One of its main objectives is to motivate farmers to make the transition to organic agriculture and hand-hold / mentor them as they make the switch. Amrita SeRVe (Self Reliant Village project) planned and helped the farmers from tillage, collection of seeds, preparation of manures and pesticides, introduction of technological innovations, modern methods in production and processing of raw materials till the marketing of products. This experiment tried at Sadivaiyal united the farmers in a pristine culture of sharing, caring, protecting and selling paddy together. This empowered them to know and bargain for their rights. This was clearly demonstrated in their farming practices, done without any instance of money-lending or of borrowing loans from banks.